Association between maternal body mass index during pregnancy, short‐term morbidity, and increased health service costs: a population‐based study. (18th September 2013) - Denison, FC; Norwood, P; Bhattacharya, S; Duffy, A; Mahmood, T; Morris, C; Raja, EA; Norman, JE; Lee, AJ; Scotland, G
<x xml:space="preserve">Abstract</x> Objective To investigate the impact of maternal body mass index (BMI, kg/m2) on clinical complications, inpatient admissions, and additional short‐term costs to the National Health Service (NHS) in Scotland. Design Retrospective cohort study using an unselected population database. Setting Obstetric units in Scotland, 2003–2010. Population A total of 124 280 singleton deliveries in 109 592 women with a maternal BMI recorded prior to 16 weeks of gestation. Methods Population‐based retrospective cohort study of singleton deliveries, with multivariable analysis used to assess short‐term morbidity and health service costs. Main outcome measures Maternal and offspring outcomes, number and duration of hospital admissions, and healthcare costs. Results Using multivariable analysis, in comparison with women of normal weight, women who were overweight, obese, or severely obese had an increased risk of essential hypertension [1.87 (1.18–2.96), 11.90 (7.18–19.72), and 36.10 (18.33–71.10)], pregnancy‐induced hypertension [1.76 (1.60–1.95), 2.98 (2.65–3.36), and 4.48 (3.57–5.63)], gestational diabetes [3.39 (2.30–4.99), 11.90 (7.54–18.79), and 67.40 (37.84–120.03)], emergency caesarean section [1.94 (1.71–2.21), 3.40 (2.91–3.96), and 14.34 (9.38–21.94)], and elective caesarean section [2.06 (1.84–2.30), 4.61 (4.06–5.24), and 17.92 (13.20–24.34)]. Compared with women of normal weight, women who were underweight, overweight, obese, or severely obese were associated with an 8, 16, 45, and 88% increase in the number of admissions, respectively, and women who were overweight, obese, or severely obese were associated with a 4, 9, and 12% increase in the duration of stay (all P < 0.001). The additional maternity costs [mean (95% CI), adjusted analyses] for women who were underweight, overweight, obese, or severely obese were £102.27 (£48.49–156.06), £59.89 (£41.61–78.17), £202.46 (£178.61–226.31), and £350.75 (£284.82–416.69), respectively. Conclusions Maternal BMI influences maternal and neonatal morbidity, the number and duration of maternal and neonatal admissions, and health service costs.